Multiscale modeling of the elasto-plastic behavior of architectured and nanostructured Cu-Nb composite wires and comparison with neutron diffraction experiments. (November 2019) - Gu, T.; Medy, J.-R.; Klosek, V.; Castelnau, O.; Forest, S.; Hervé-Luanco, E.; Lecouturier–Dupouy, F.; Proudhon, H.; Renault, P.-O.; Thilly, L.; Villechaise, P.
Abstract: Nanostructured and architectured copper niobium composite wires are excellent candidates for the generation of intense pulsed magnetic fields ( ∼ 100 T ) as they combine both high strength and high electrical conductivity. Multi-scaled Cu-Nb wires are fabricated by accumulative drawing and bundling (a severe plastic deformation technique), leading to a multiscale, architectured, and nanostructured microstructure exhibiting a strong fiber crystallographic texture and elongated grain shape along the wire axis. This paper presents a comprehensive study of the effective elasto-plastic behavior of this composite material by using two different approaches to model the microstructural features: full-field finite elements and mean-field modeling. As the material exhibits several characteristic scales, an original hierarchical strategy is proposed based on iterative scale transition steps from the nanometric grain scale to the millimetric macro-scale. The best modeling strategy is selected to estimate reliably the effective elasto-plastic behavior of Cu-Nb wires with minimum computational time. Finally, for the first time, the models are confronted to tensile tests and in-situ neutron diffraction experimental data with a good agreement. Highlights: A hierarchical homogenization strategy is proposed to describe the elastoplastic behavior of architectured and nanostructured Cu-Nb. The mean field effective model is identified by means of full field finite element simulations. The model accounts for the double <100> - <111> fiber texture in Copper and the <110> fiber texture in Niobium. Elastic strains were measured in the individual copper and niobium texture components by neutron diffraction during in situ tensile testing. Experiments and theory show consistently that plastic activity occurs in <100> oriented grains at a higher applied macroscopic stress than in <111> grains in tensile loading along the wire direction.